Sustainable intensification of cassava cropping systems - Omondi, J.O.; Gbegbelegbe, S.; Kadwala, P.; Msukwa, W.; Kyei-Boahen, S.; Chinwada, P.; Akinwale, G.; Alene, A. (International Institute of Tropical Agriculture, 2025)
In Malawi, shrinking farmland, poor soil health, limited crop diversity, climate change, and crop varieties that are unsuitable and not specific for various agro-ecologies are major challenges affecting yields. This study aimed to develop innovations to improve crop yields, soil health, incomes, and climate resilience. Different nutrient combinations and intercropping arrangements were tested—alternating rows of cassava and cowpeas—across three agro-ecological zones over two seasons (2020–2022). Cassava received either 0 or 60 kg N ha⁻¹ (split into two applications), while cowpea received either 0 or 30 kg N ha⁻¹. The most promising treatments were then tested on farms in seven districts for another two seasons (2022–2024). Farmers evaluated these treatments based on yield, acceptance, and economic benefits. Results showed that intercropping cassava with cowpea (variety Sudan 1) in alternating single rows using 60 kg N ha⁻¹ for cassava and 30 kg N ha⁻¹ for cowpea significantly outperformed traditional practices. This system improved grain and storage root yield, land use efficiency, farmer preference, and profitability. Additionally, Sudan 1 cowpea yielded better than IT82E-16, highlighting the importance of variety selection in intercropping. Given these benefits, we recommended the release and adoption of these technologies to restore soil health, enhance climate adaptation, diversify crops and nutrition, and boost smallholder farmers’ incomes. The Agricultural Technology Clearing Committee of Malawi (ATCC) approved them for release.